Peran Skor Brixia sebagai Prediktor Kejadian Coronavirus Disease-19 (COVID-19)-associated Hemostatic Abnormalities (CAHA) Berdasarkan Kadar D-dimer - Fiona, Fiona; Margiani, Ni Nyoman; Sitanggang, Firman Parulian; Eka Putra, I Wayan Gede Artawan; Anandasari, Pande Putu Yuli; Ayusta, I Made Dwijaputra (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: Coronavirus Disease-19 (COVID-19) is a systemic disease that causes complications in respiratory system and coagulopathy, which is called COVID-19-associated hemostatic abnormalities (CAHA). The Brixia chest X-ray scoring system may benefit in detecting CAHA. This study aims to investigate the role of the Brixia score as a predictor of CAHA based on D-dimer levels. Methods: This was a cross-sectional study that used medical records from Radiology Installation, Sanglah General Hospital, Bali, during August 2020 until August 2021. Subjects were confirmed and hospitalized COVID-19 patients with mild to critical degree and aged 18-59 years old. Any other pulmonary diseases than COVID-19 in X-ray was excluded. Brixia score was determined independently and blindly determined by two radiologists. The incidence of CAHA was defined as an elevation of D-dimer in pulmonary COVID-19. We conducted interobserver Bland-Altman, followed by correlation test, receiver operating characteristic (ROC) analysis, and multiple logistic regression test to control for confounding factors. Result: This study included 70 subjects selected through random sampling. We found a positive correlation between the Brixia score and D-dimer levels (r=0.329, p less than 0.05). The ROC analysis indicated that a Brixia score cut-off ≥10 is the best predictor of CAHA, with a positive predictive value of 95.8% and a negative predictive value of 40.9%. Subjects with a Brixia score ≥10 were found to have a higher risk of developing CAHA (aOR 14.78, p less than 0.05) after controlling for age, gender, nutritional status, and comorbidities. Conclusion: There was a statistically significant association between Brixia score and CAHA in COVID-19 patients based on D-dimer levels. The Brixia score could be used as a predictor of CAHA with the cut-off value ≥10.